Antimicrobial Properties of Food Nanopackaging: A New Focus on Foodborne Pathogens - Anvar, Amir Ali; Ahari, Hamed; Ataee, Maryam (Frontiers in Microbiology, 2021)
Foods products contaminated by foodborne pathogens (bacteria, parasites, and viruses) cause foodborne diseases. Today, great efforts are being allocated to the development of novel and effective agents against food pathogenic microorganisms. These efforts might have a possible future effect in coronavirus disease 2019 (COVID-19) pandemic. Nanotechnology introduces a novel food packaging technology that creates and uses nanomaterials with novel physiochemical and antimicrobial properties. It could utilize preservatives and antimicrobials to extend the food shelf life within the package. Utilizing the antimicrobial nanomaterials into food packaging compounds typically involves incorporation of antimicrobial inorganic nanoparticles such as metals [Silver (Ag), Gold (Au), Copper (Cu)], and metal oxides [Titanium dioxide (TiO2), Silicon oxide (SiO2), Zinc oxide (ZnO)]. Besides, intelligent food packaging has been explored for recognition of spoilage and pathogenic microorganisms. This study focused on antimicrobial aspects of nanopackaging and presented an overview of antibacterial properties of inorganic nanoparticles. This article also provides information on food safety during COVID-19 pandemic.